The 'real' explanation of the Feldstein–Horioka puzzle. Issue 2 (19th January 2017) - Ford, Nicholas; Horioka, Charles Yuji
ABSTRACT: This article shows that global capital markets cannot, by themselves, achieve net transfers of financial capital between countries and that both the integration of global financial markets and the integration of global goods markets are needed to achieve net transfers of capital between countries. Frictions (barriers to mobility) in one or both of these markets can impede net transfers of capital between countries, produce the Feldstein and Horioka (1980) results and prevent real interest rates from being equalized across countries. Moreover, there is empirical evidence that barriers to the mobility of goods and services are an important obstacle to international capital mobility.